2017
DOI: 10.1364/optica.4.000185
|View full text |Cite
|
Sign up to set email alerts
|

Short-wave infrared LEDs from GeSn/SiGeSn multiple quantum wells

Abstract: Group IV photonics is on the way to be integrated with electronic circuits, making information transfer and processing faster and more energy efficient. Light sources, a critical component of photonic integrated circuits, are still in development. Here, we compare Multi-Quantum-Well (MQW) light emitting diodes (LEDs) with Ge0.915Sn0.085 wells and Si0.1Ge0.8Sn0.1 to a reference Ge0.915Sn0.085 homojunction LED. Material properties as well as band structure calculations are discussed, followed by optical investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 23 publications
0
71
0
Order By: Relevance
“…Heterostructures like presented in Ref. 38 , combined with tensile strain, would strongly improve the carrier confinement at higher temperatures and, consequently, further decrease the threshold pump power density. QWs heterostructures design allows the separation of the active region from interface defects without using a layer transfer technology, which is desirable for low-cost, high yield fabrication.…”
Section: /12mentioning
confidence: 97%
“…Heterostructures like presented in Ref. 38 , combined with tensile strain, would strongly improve the carrier confinement at higher temperatures and, consequently, further decrease the threshold pump power density. QWs heterostructures design allows the separation of the active region from interface defects without using a layer transfer technology, which is desirable for low-cost, high yield fabrication.…”
Section: /12mentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9] The successful demonstration of direct bandgap GeSn light emitting diodes (LEDs), and optically-pumped GeSn lasers, [10][11][12][13][14] indicates the great potential of GeSn for Si-based light sources. GeSn LEDs with double heterostructures (DHS) 11,[15][16][17][18][19][20][21][22] and quantum wells (QWs) [23][24][25][26][27][28][29][30][31] have been reported. It is generally acknowledged that the QW structures could be applied to the LEDs and lasers to improve their device performance.…”
mentioning
confidence: 99%
“…23,24,32,33 By engineering the Si and Sn composition, using SiGeSn as barrier, the carrier confinement in the QW was improved compared to those using Ge as barrier. Moreover, the band structure analysis and characterization results indicated that the direct bandgap well could be achieved by using high-Sn GeSn material, 23,24 which is desired for the improvement of the light emission efficiency. However, an in-depth study including detailed band structure calculation and optical transition has not been performed on a direct bandgap GeSn QW so far.…”
mentioning
confidence: 99%
“…Considering that band gap can be adjusted by adding Sn content, GeSn material can be applied for light emitting devices, including laser and LED. It has been reported that the related work is underway in laser [38][39][40] and light emission [41][42][43] . However, most of work is just focused on optical pumping at low temperature and the luminous efficiency is low.…”
Section: Outlook and Summarymentioning
confidence: 99%